The Impact of Lifelong Learning Programs on Employability and Career Transitions - Michael Han; Fatma El-Farabi (PT Mutiara Bustan Ilmu, 2025)
Lifelong learning programs have become essential in promoting employability and facilitating career transitions in dynamic labor markets. This study investigates how participation in continuous learning initiatives enhances individuals’ skills, adaptability, and professional mobility. Using a mixed-methods approach, data were collected from participants across multiple industries to assess skill acquisition, career progression, and perceived employability. Findings indicate that lifelong learning significantly improves technical and soft skills, fosters self-efficacy, and supports smoother transitions between careers. The study also highlights the role of lifelong learning in promoting social inclusion and addressing skill mismatches. Implications suggest that policymakers and organizations should prioritize accessible, high-quality lifelong learning programs to maximize workforce resilience and economic growth.